The Usage of Tests in Teaching Ukrainian Punctuation (on the material of the theme “Stages of punctuation development”) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the difficulties faced in the process of teaching Ukrainian punctuation. There outlined the ways of their overcoming and grounded the perspectives of practicability of establishing and using the computer program “Tests”. Moreover there suggested a system of tests to follow the stages of punctuation development since old time till present.
Keywords: Ukrainian punctuation; stages of punctuation development; tests